The Use of Aspirin for the Treatment of Malignancies: Review Study - Ra’ouf Alnsour, Dana Ayman Abdel; Alkhatib, Ahed J (European Scientific Journal, ESJ, 2016)
The present review study reviewed the literature for the possible therapeutic roles of aspirin against tumors. Aspirin has various therapeutic properties among which is the anti-inflammatory property. Epidemiological studies have proved the efficacy of long term use of aspirin in reducing the incidence of colorectal cancer by up to 30%, and the cancer risk as well. Although no exact mechanism has been entirely proposed so far to explain the antineoplastic effect of aspirin against cancer, two mechanisms have been under focus, the first is related to its anti-inflammatory properties which are thought to suppress the inflammatory mediators and to inhibit carcinogenic mechanisms, and the other mechanism is through the deactivation of COX2. We would like to raise the possibility for aspirin to be regularly involved in preventive mechanisms.